Public Service Quality and Building Coordinated Policy: An Analytical Study of Jamkesmas And Jamkesda Implementation - Hevi Kurnia Hardini (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2013)
This study will examine the implementation of Jamkesmas (Jaminan Kesehatan Masyarakat-Health Insurance Scheme for People) and Jamkedsa (Jaminan Kesehatan Masyarakat Daerah-Health Insurance Scheme for Local People). Both are innovative policies in term of health financing, since they reflect more the spirit of insurance compared to the previous policies which were merely about financial aid. However, these policies do not reflect the ideals of policy coordination. Several theoretical reviews about social health insurance are applied to figure out the spirit of Indonesian health insurance sociologically and culturally. The Colebatch’s framework of vertical and horizontal dimensions of policy is used as the main tool of analysis for measuring whether both Jamkesmas and Jamkesda are categorized as coordinated policies or not. Qualitative research approach is used as the method in order to gain in-depth information about the current polemic of Jamkesmas and Jamkesda implementations. Qualitative analysis method is applied during the process of analysis. The secondary data will be collected, sorted, coded and analyzed. Those several steps aim to cross check the validity of each data for answering the research questions. The result of this study shows that Jamkesmas and Jamkedsa lack of coordination during the process of policy making which has led to complicated problems at the implementation stage namely: the lawsuit/multiple interpretations of the law, unstructured policy stages at the vertical level, complicated problems at horizontal stages and conflict among institutional governments. Moreover, the nature of policy coordination in Indonesia is still reactive. This fact causes policy inconsistency which has the effect of law uncertainty and poor quality of public services.